MUHAMMADIYAH: GERAKAN MODERNISME ISLAM - Haedar Nashir (Tajdida: Jurnal Pemikiran dan Gerakan Muhammadiyah, 2016)
This paper reveals about the Muhammadiyah movement which is very strategic, it is reformist-modern Islamic movement that takes the mid position with Islamic view “progressive fondation”.  Muhammadiyah view can be used as the fondation of the modern world enters a new era of the twenty-first century, which has entered the second century with the theme "progressive Islam" and "Enlightenment Movement". The agenda is how to give the epistemological and methodological foundation for Muhammadiyah movement in the second century more strongly so as to present an alternative praxis.